Is Low-Level Laser Therapy Effective for Pain Control After the Surgical Removal of Unerupted Third Molars? A Randomized Trial - Santos, Pâmela Letícia; Marotto, Ana Paula; Zatta da Silva, Thaiz; Bottura, Mariele Pecorali; Valencise, Mayra; Marques, Daniela Oliveira; Queiroz, Thallita Pereira (Elsevier, 2020)
Purpose: One of the main challenges after extraction of unerupted third molars is pain control, and one of the treatments for pain control is low-level laser therapy (LLLT). Thus, this study aimed to assess the effectiveness of LLLT for pain control after extraction of lower third molars. Materials and Methods: This randomized, double-blind, split-mouth study included patients who required bilateral extraction of unerupted lower third molars. Patients received LLLT on 1 side (laser group) but not on the opposite side (control group). On the experimental side, each patient received a laser application at 5 intraoral points for 30 seconds per point. This procedure was simulated on the control side. The pain control response was assessed with a modified pain visual analog scale at the following times: immediately after surgery (T0), after laser application (T1), 24 hours after surgery (T2), 48 hours after surgery (T3), and 72 hours after surgery (T4). Results: Thirty-two patients, 56.25% of whom were women, underwent extraction; the average age was 22.2 years. At the times analyzed, the laser group presented better results than the control group. As for the times, there were differences in pain scores between T0 (8.03 ± 14.87) and T3 (2.66 ± 4.23), as well as T4 (3.36 ± 7.83), in the laser group and differences between T0 (19.76 ± 26.66) and T3 (7.11 ± 10.76), as well as T4 (6.26 ± 13.14), in the control group. Conclusion: LLLT was effective in reducing pain after surgical removal of unerupted third molars. At T3 and T4, pain reduction in relation to T0 was noted in both groups.